1996
DOI: 10.1002/j.1460-2075.1996.tb01032.x
|View full text |Cite
|
Sign up to set email alerts
|

TolA central domain interacts with Escherichia coli porins.

Abstract: TolA is an inner membrane protein with three domains: a transmembrane N‐terminus and periplasmic central and C‐terminal domains. The interaction of TolA with outer membrane porins of Escherichia coli was investigated. Western blot analyses of cell extracts with anti‐TolA antibodies indicated that TolA forms high molecular weight complexes specifically with trimeric OmpF, OmpC, PhoE and LamB, but not with OmpA. The interaction of purified TolA domains with purified porins was also studied. TolA interacted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 35 publications
7
78
0
Order By: Relevance
“…It was implied that once the N2 domain binds to the tip of the pilus, its affinity for the N1 domain decreases, leaving this part of g3p free to interact with its secondary receptor. After depolymerization of the pilus, the released N1 domain can interact with the CT part of TolA localized on the inside of the outer membrane (7,9,27). Our observation of a second F-pilus-interacting domain (L1) could reflect the fact that amino acid residues 68 to 86 of g3p might constitute the pilus-binding epitope together with residues in the N2 domain.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It was implied that once the N2 domain binds to the tip of the pilus, its affinity for the N1 domain decreases, leaving this part of g3p free to interact with its secondary receptor. After depolymerization of the pilus, the released N1 domain can interact with the CT part of TolA localized on the inside of the outer membrane (7,9,27). Our observation of a second F-pilus-interacting domain (L1) could reflect the fact that amino acid residues 68 to 86 of g3p might constitute the pilus-binding epitope together with residues in the N2 domain.…”
Section: Discussionmentioning
confidence: 77%
“…N2 mediates the interaction with the first bacterial receptor, the F pilus (1). The first domain (N1) is believed to interact with the second receptor, the TolQRA protein complex, spanning the periplasmic space and the inner membrane (5,9,27,31). It has previously been shown that phage with only the N1 and the CT domains on its surface will infect at a drastically reduced level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the exact function is not known, current research focuses on the link between Tol-Pal proteins and porins, lipopolysaccharides (LPS), or O-antigen biogenesis. It has been shown that the central domain of the TolA protein, as well as the TolB protein, interacts in vitro with major OM trimeric porins such as OmpF, OmpC, LamB, and PhoE in the presence of sodium dodecyl sulfate (150,554). TolA and TolB do not interact with OmpA or the OM denaturated porins.…”
Section: Tol-dependent Colicinsmentioning
confidence: 99%
“…This role is probably important, as homologs of the Tol proteins are found in several gram-negative bacteria, including Haemophilus influenzae (7), Brucella abortus (22), Pseudomonas putida (21), and Pseudomonas aeruginosa (18). The central domain of TolA specifically interacts with trimeric porins such as OmpC, OmpF, LamB, and PhoE (9). Such interactions have been proposed to be involved in the process of assembly of outer membrane trimeric porins and to be relevant to the function of the Tol system.…”
mentioning
confidence: 99%